2013
DOI: 10.1111/ijd.12231
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic antimalarial drugs and the triggering of psoriasis – do we need disease‐specific guidelines for the management of patients with psoriasis at risk of malaria?

Abstract: Despite the increased awareness, antimalarials-triggered psoriasis is still diagnosed. Fortunately, the current artemisinin-based antimalarial treatment can be safely offered to susceptible individuals. Additionally, prophylaxis with doxycycline or the combination atovaquone-proguanil could be a safe suggestion for malaria prophylaxis in psoriatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 12 publications
1
11
0
1
Order By: Relevance
“… 127 It is reported that induction or exacerbation of psoriasis is observed in lichen planopilaris (a 40-year-old female) and psoriatic arthritic (a 37-year-old primigravida) patients treated with hydroxychloroquine. 128 An acute gluteal abscess after an injection of chloroquine has also been reported. 129 Acute generalized exanthematous pustulosis has been reported in Canada as an adverse reaction to hydroxychloroquine.…”
Section: Adverse Effectsmentioning
confidence: 96%
“… 127 It is reported that induction or exacerbation of psoriasis is observed in lichen planopilaris (a 40-year-old female) and psoriatic arthritic (a 37-year-old primigravida) patients treated with hydroxychloroquine. 128 An acute gluteal abscess after an injection of chloroquine has also been reported. 129 Acute generalized exanthematous pustulosis has been reported in Canada as an adverse reaction to hydroxychloroquine.…”
Section: Adverse Effectsmentioning
confidence: 96%
“… 10 Hydroxychloroquine and other synthetic antimalarial drugs may induce psoriasis by interfering with the integrity of the epidermal barrier. 11 Proposed mechanisms include inhibition of epidermal transglutaminase enzymes or interfering with cholesterol metabolism, both of which are important for the structure of the epidermal barrier. 11 The rash occurs quickly, typically within 4–12 weeks after drug introduction.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Proposed mechanisms include inhibition of epidermal transglutaminase enzymes or interfering with cholesterol metabolism, both of which are important for the structure of the epidermal barrier. 11 The rash occurs quickly, typically within 4–12 weeks after drug introduction. 2 Thalidomide was reported to induce psoriasis in 1 case report, with disease induction within 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…37 , 38 Furthermore, there have been cases reported of psoriasis exacerbation with the use of hydroxychloroquine as immunomodulating treatment for lichen planopilaris and psoriatic arthritis. 39 Rarely, these antimalarial drugs are linked to induction of psoriasis. 40 The latency period of psoriasis exacerbation is usually between 4 and 12 weeks.…”
Section: Traditionally Reported Drug-associationsmentioning
confidence: 99%